CEO Characteristics and Timeliness of Financial Reporting of Vietnamese Listed Companies - Khuong, Nguyen Vinh; Vy, Nguyen Thi Xuan (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
Timeliness of financial reporting is a qualitative characteristics that enhance the usefulness of information and significant to users of financial statements. This study examines that board diversity (GENDERCHAIR), CEO age (CEOAGE) have impact on audit report timeliness. The sample of this study comprises of 100 companies listed on Vietnamese Stock Exchange in the period 2012 - 2014. Ordinary Least Square (OLS) regression analysis are performed to test the audit report timeliness determinants . Using quantitative research methods, findings found that there is a significant positive relationship between board diversity on timeliness of financial reporting while proxy variables of the CEO age have a significant negative relationship with timeliness of financial reporting. . This paper extends prior research by addressing the potential effects of female executives on timeliness of financial reporting.   Keywords Chief executive officer, timeliness of financial reporting, listed firms, Vietnam References Abdullah, S. N., “Board composition, audit committee and timeliness of corporate financial reports in Malaysia”, Corporate Ownership & Control, 4 (2006) 4, 33-45. Al-Ajmi, J., “Audit and reporting delays: Evidence from an emerging market”, Advances in Accounting, 24 (2008) 2, 217-226 Al-Akra, M., Eddie, I. A., & Ali, M. J., “The influence of the introduction of accounting disclosure regulation on mandatory disclosure compliance: Evidence from Jordan”, The British Accounting Review, 42 (2010) 3, 170-186. Alkhatib, K., & Marji, Q., “Audit reports timeliness: Empirical evidence from Jordan”, Procedia-Social and Behavioral Sciences 62 (2012), 1342-1349. AL-Shwiyat, Z. M. M., “Affecting factors on the timing of the issuance of annual financial reports: empirical study on the jordanian public shareholding companies”, European Scientific Journal, 9 (2013) 22, 407-423. Ashton, R. H., Graul, P. R., & Newton, J. D., “Audit delay and the timeliness of corporate reporting”, Contemporary Accounting Research, 5 (1989) 2, 657-673. Bamber, E. M., Bamber, L. S., & Schoderbek, M. P., “Audit structure and other determinants of audit report lag: An empirical analysis”, Auditing, 12 (1993) 1, 1-23. Bergstresser, D. and Philippon, T., “CEO incentives and earnings management”, Journal of Financial Economics, 80 (2006) 3, 511-529. Bertrand, M. and Schoar, A., “Managing with Style: The Effect of Managers on Firm Policies”, The Quarterly Journal of Economics, 118, (2003) 4, 1169–1208 Carmichael, D., Ghosh, A. and Lee, H., “Causes and consequences of abnormally long audit reporting lags”, in Bishop, C. C., ed. American Accounting Association Annual Meeting, Colorado, Wednesday August 10, 2011, Denver, Colorado: American Accounting Association (2011), 1-41. Catalyst, “The bottom line: Connecting corporate performance and gender diversity” (2004). Che-Ahmad, A., & Abidin, S., “Audit delay of listed companies: A case of Malaysia”, International business research, 1 (2009) 4, 32. Cohen, J., Krishnamoorthy, G., & Wright, A. M., “Corporate governance and the audit process”, Contemporary accounting research, 19 (2002) 4, 573-594. Ettredge, M. L., Sun, L. and Li, C., “The impact of SOX section 404 internal control quality assessment on audit delay in the SOX era”, Auditing: A Journal of Practice & Theory, 25 (2006) 2, 1-23. Ezat, A., & El-Masry, A., “The impact of corporate governance on the timeliness of corporate internet reporting by Egyptian listed companies”, Managerial finance, 34 (2008) 12, 848-867. Feng, M., Ge, W., Luo, S., & Shevlin, T., “Why do CFOs become involved in material accounting manipulations?”, Journal of Accounting and Economics, 51 (2011) 1, 21-36. Francis, J., Huang, A. H., Rajgopal, S. and Zang, A. Y., “CEO reputation and earnings quality”, Contemporary Accounting Research, 25 (2008) 1, 109-147. Hambrick, D. C. and Mason, P. A., “Upper echelons: The organization as a reflection of its top managers”, The Academy of Management Review, 9 (1984) 2, 193-206. Hazarika, S., Karpoff, J. M. and Nahata, R., “Internal corporate governance, CEO turnover, and earnings management”, Journal of Financial Economics, 104 (2012) 1, 44-69. Inchausti, B. G., “The influence of company characteristics and accounting regulation on information disclosed by Spanish firms”, European accounting review, 6 (1997) 1, 45-68. Jiang, F., Zhu, B. and Huang, J., “CEO's financial experience and earnings management”, Journal of Multinational Financial Management, 23 (2013) 3, 134-145. Jiang, J. X., Petroni, K. R., & Wang, I. Y,. “CFOs and CEOs: Who have the most influence on earnings management?”, Journal of Financial Economics, 96 (2010) 3, 513-526. Khademi, V., “The relation between investment opportunities and asset growth among the companies accepted in Tehran Stock Exchange”, Accountant 207 (2009), 74-77. Khasharmeh, H. A., & Aljifri, K., “The timeliness of annual reports in Bahrain and the United Arab Emirates: An empirical comparative study”, The International Journal of Business and Finance Research, 4 (2010) 1, 51-71. Klein, A., “Audit committee, board of director characteristics, and earnings management”, Journal of Accounting and Economics, 33 (2002) 3, 375-400. Knechel, W. R. and Sharma, D. S., “Auditor-provided non audit services and audit effectiveness and efficiency: Evidence from pre- and post-SOX audit Report Lags”, Auditing: A Journal of Practice & Theory, 31 (2012) 4, 85-114. Knechel, W. R., Sharma, D. S. and Sharma, V. D., “Non-audit services and knowledge spillovers: Evidence from New Zealand”. Journal of Business Finance & Accounting, 39 (2012) 1-2, 60-81. Leventis, S., & Weetman, P., “Timeliness of financial reporting: applicability of disclosure theories in an emerging capital market”, Accounting and Business Research, 34 (2004)1, 43-56. Mande, V. and Son, M., “Do audit delays affect client retention?”, Managerial Auditing Journal, 26 (2011) 1, 32-50. Mohamad-Nor, M. N., Shafie, R. and Wan-Hussin, W. N., “Corporate governance and audit report lag in Malaysia”, Asian Academy of Management Journal of Accounting & Finance, 6 (2010) 2, 57-84. Mudrack, P., “Age-related differences in a Machiavellian adult sample”, Psychology Report, 64 (1989) 2, 1947–1950. Munsif, V., Raghunandan, K. and Rama, D. V., “Internal control reporting and audit report lags: Further evidence”, Auditing: A Journal of Practice & Theory, 31 (2012) 3, 203-218. Nelson, S. N., & Shukeri, S. N., “Corporate governance and audit report timeliness: evidence from Malaysia”, In Accounting in Asia, (2011), 109-127. Emerald Group Publishing Limited. Owusu-Ansah, S., “Timeliness of corporate financial reporting in emerging capital markets: Empirical evidence from the Zimbabwe Stock Exchange”, Accounting and business research, 30 (2000) 3, 241-254. Owusu-Ansah, S., & Leventis, S., “Timeliness of corporate annual financial reporting in Greece”, European Accounting Review, 15 (2006) 2, 273-287. Peterson, D., A. Rhoads, and B. C. Vaught., “Ethical beliefs of business professionals: A study of gender, age and external factors”, Journal of Business Ethics, 31 (2001) 3, 225–233. Rafiee, S. Z., Rafiee, S. Z., & Heidarpoor, F., “The effective factors of financial information quality in listed companies on Tehran Stock Exchange”, International Journal of Accounting and Financial Reporting, 4 (2014) 2, 201. Robinson, G., & Dechant, K., “Building a business case for diversity”, The Academy of Management Executive, 11 (1997) 3, 21-31. Sundaram, R. K., & Yermack, D. L., “Pay me later: Inside debt and its role in managerial compensation”, The Journal of Finance, 62 (2007) 4, 1551-1588. Türel, A., “Timeliness of financial reporting in emerging capital markets: Evidence from Turkey”, Istanbul University Journal of the School of Business, 39 (2010) 2, 227-240. Walt, N., & Ingley, C., “Board dynamics and the influence of professional background, gender and ethnic diversity of directors”, Corporate Governance: An International Review, 11 (2003) 3, 218-234. Wan-Hussin, W. N. and Bamahros, H. M., “Do investment in and the sourcing arrangement of the internal audit function affect audit delay, Journal of Contemporary Accounting & Economics, 9 (2013) 1, 19-32. Wilson, M., & Wang, L. W., “Earnings management following chief executive officer changes: the effect of contemporaneous chairperson and chief financial officer appointments”, Accounting & Finance, 50 (2010) 2, 447-480. Younes H., “The relationship between financial reporting timeliness and attributes of companies listed on Egyptian Stock Exchange: An empirical study”, Internal Auditing & Risk Management 6 (2011)3. Zhang, Y., & Wiersema, M. F., “Stock market reaction to CEO certification: The signaling role of CEO background”, Strategic Management Journal, (2009), 693-710.